Women's Knowledge and Concern about Breast Cancer - Kafi Mohammed Nasir Al Asadi (Kufa Journal for Nursing Sciences)
Background: Breast cancer is the most common malignant tumor among women and the second most common type of cancer after lung cancer, 10.4% of all cancer incidences, and the fifth most of cancer deaths. Breast cancer is the top cancer in Iraqi's women, comprising about 34% of all females cancer, and it is the second leading cause of cancer related to mortality in women today after lung cancer. In Iraq, breast cancer constitute about one third of total cancer.